2022
DOI: 10.3390/ijms231810960
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor Subtypes Elicit a Distinct Gene Expression Profile of Endothelial-Derived Factors Implicated in Atherosclerotic Plaque Vulnerability

Abstract: In the presence of established atherosclerosis, estrogens are potentially harmful. MMP-2 and MMP-9, their inhibitors (TIMP-2 and TIMP-1), RANK, RANKL, OPG, MCP-1, lysyl oxidase (LOX), PDGF-β, and ADAMTS-4 play critical roles in plaque instability/rupture. We aimed to investigate (i) the effect of estradiol on the expression of the abovementioned molecules in endothelial cells, (ii) which type(s) of estrogen receptors mediate these effects, and (iii) the role of p21 in the estrogen-mediated regulation of the af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 121 publications
1
4
0
Order By: Relevance
“…In goat oviductal epithelial cells, estradiol can induce TIMP-1 expression [23]. A similar observation was reported in human aortic endothelial cells under inflammatory conditions but not normal conditions [24]. Thus, there is a possibility that TIMP-1 may be a gene that escapes X-chromosome inactivation during inflammatory events leading to severe ARDS.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In goat oviductal epithelial cells, estradiol can induce TIMP-1 expression [23]. A similar observation was reported in human aortic endothelial cells under inflammatory conditions but not normal conditions [24]. Thus, there is a possibility that TIMP-1 may be a gene that escapes X-chromosome inactivation during inflammatory events leading to severe ARDS.…”
Section: Discussionsupporting
confidence: 71%
“…Different from many X-linked genes, Anderson and colleagues reported that human TIMP-1 is prone to reactivation or variable in its inactivation [22]. In addition, it has been reported that estradiol can significantly induce TIMP-1 expression in goat oviductal epithelial cells [23] and human aortic endothelial cells under inflammatory conditions [24]. Thus, there is a possibility that TIMP-1 may serve as a sex-specific biomarker.…”
Section: Introductionmentioning
confidence: 99%
“…An additional 12 AH samples from each group were subjected to ELISA. AH proteins were measured using the human metallopeptidase inhibitor 1 (TIMP1) (DTM100; R&D Systems), angiopoietin-related protein 7 (ANGPTL7), and Fc fragment of IgG binding protein (FCGBP) ELISA Kit (CSB-EL001715HU, CSB-EL008536HU; Cusabio Technology) according to the manufacturer's instructions [48,49]. Briefly, all samples were brought to room temperature before use and were assayed in duplicate.…”
Section: Enzyme-linked Immunosorbent Assay (Elisa)mentioning
confidence: 99%
“…In the absence of inflammatory stimuli, estrogens protect the initial stages of atherosclerosis in both sexes. However, in conditions such as established atherosclerosis, which can be considered a low-grade inflammatory state, E2 can destabilize atherosclerotic plaques by inducing molecules like MCP-1, matrix metalloproteinases (specifically MMP-2 and MMP-9), and TNF-α [41][42][43][44]. When atherosclerotic lesions are present, the altered expression of estrogen receptors on the vascular wall further exacerbates arterial wall damage [41,45].…”
Section: Sex-specific Relationship Of Oxldl and Crp With E2 And E2/tmentioning
confidence: 99%